The influence of Self-efficacy amongst students towards Interest to continue College education: A Study on SMA Negeri 4 Karawang - Ayu Ganis Hemasti, Randwitya; Ainy Sa’dijah, Nur; Nursjanti, Farida (International Journal of Psychosocial Rehabilitation, 2020)
The phenomena of many students who will graduate from SMA 4 Karwang who experience confusion in making decisions to determine between proceeding to college or work. The difficulty in making the choice to continue college or work is a lack of confidence in the ability of oneself so that the students faced feelings of fear wrong in taking a decision. This study aims to determine Contribution Self-efficacy Against Interest Continuing College in students SMA Negeri 4 Karawang. The research method used in this research is quantitative with causal associative research designs. The population in the study where study were students of class XII senior high school 4 Karawang school year 2019-2020 which numbered 355 person. Sampling technique using nonprobability sampling with type sampling Kouta. The sampling of kauta is determined by degerming the sample of the population that has certain features up to the desired amount (Kouta). The size of the sampel using the formula slovin with sample eror rates 5% then the results obtained 188 people studen. Data collection using a questionnaire. Hypothesis testing between self-efficacy of the interest in continuing college has an r value of 0,410 with a significace valau of 0,000 (p<0,05). This shows that there is a contribution between self-efficacy to the interest in continuing higer education. The amount of contribution is show by the variabel of self-efficacy to interest in continuing to tertiary education to ask to continue tertiary education contributed 0.168 or equal to 16,8%. This implies that self-efficacy variables affect the interest in continuing college.